The Influence of Professional Competence and Organizational Climate on Teacher Performance in Vocational High Schools - M Teguh Saefuddin; Sholeh Hidayat; Yayat Ruhiat (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Teacher performance is a key factor in achieving educational goals, because teachers are required to be able to realize the expectations of various parties, especially the community who entrust their children's education to the school. However, reality shows that there are still many teachers who show that their performance is not optimal. This is due to the low professional competence possessed and the lack of conducive organizational climate in the school environment. This study aims to analyze the influence of professional competence and organizational climate on teacher performance. The type of research used is quantitative research with an explanatory approach. The subjects in this study are all teachers at SMKN 7 Pandeglang which totals 54 people. Data collection is carried out through a questionnaire that has been tested for validity and reliability. Data were analyzed using multiple linear regression techniques to test the relationship between independent variables (professional competence and organizational climate) and bound variables (teacher performance). The results showed that professional competence contributed 50.48% to teacher performance, while organizational climate contributed 23.18%. Simultaneously, professional competence and organizational climate contributed to teacher performance by 30.82%. The conclusion of this study is that there is a significant influence between professional competence and organizational climate on teacher performance. The implication is that improving professional competence and creating a positive organizational climate need to be the main focus in efforts to improve the quality of education in schools.